How to Improve Mining Tax Administration and Collection Frameworks : A Sourcebook - Guj, Pietro; Bocoum, Boubacar; Limerick, James; Meaton, Murray; Maybee, Bryan (World Bank, Washington, DC, 2014)
Governments of mineral-rich countries formulate and use a variety of financial imposts to collect a share of the revenue generated by mining companies. Instruments include the full range of taxes, fees, and charges that generally apply to all normal commercial operations. In addition to these measures, most governments use mineral royalties along with variations to the corporate taxation measures, customs duties, and value-added taxes that apply just to mining. This sourcebook focuses on mineral royalties and on other taxation measures that are specific to mining activities, with particular emphasis on imposts of common application in most developing countries, which may create challenges in their administration. The legislative framework establishing these taxes in developing countries that are experiencing an accelerated pace of resource development is in most cases relatively modern and largely adequate, but the supporting administrative capability, procedures, and systems have tended to lag behind. This sourcebook presents a practical overview of how to analyze and improve the administrative frameworks and systems for mineral royalties and other taxes specific to mining. This sourcebook provides a structured approach to help the ministries of finance and mines analyze and improve their effectiveness and efficiency in handling common issues and challenges; avoid duplication of effort; and overcome the organizational, structural, and resourcing difficulties generally encountered in the administration of various elements of mining regimes.